2022
DOI: 10.29267/mxjb.2022.7.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the tomato quality fertilized with sargassum extract from the Mexican Caribbean and mycorrhizae

Abstract: Tomato is one of the agricultural products with the highest economic value in the world, for its production agrochemicals are generally used, however, their excessive use has caused environmental problems. A commercial sargassum extract was evaluated as a fertilizer for tomato cultivation, it was applied at 2 (N2), 5 (N5) and 8% (N8), with and without inoculation (400 spores) of arbuscular mycorrhizal fungi; mineral fertilization (C+) and no fertilization (C-) were used as controls. With C+ the highest number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…low lying islands) as decaying seaweed can contaminate nearby aquifers [55]. On the positive side, beneficial impacts include: the potential for reuse of brown algae in locally or commercially produced items such as fish feed for aquaculture, biogas and as a plant fertiliser [36,[56][57][58]. The overall lack of evidence of societal impacts for some of the brown algae events may be an artefact of the method used to search for papers, or it could reflect an absence of any evidence, pointing to the need for research on the social impacts of these events.…”
Section: Resultsmentioning
confidence: 99%
“…low lying islands) as decaying seaweed can contaminate nearby aquifers [55]. On the positive side, beneficial impacts include: the potential for reuse of brown algae in locally or commercially produced items such as fish feed for aquaculture, biogas and as a plant fertiliser [36,[56][57][58]. The overall lack of evidence of societal impacts for some of the brown algae events may be an artefact of the method used to search for papers, or it could reflect an absence of any evidence, pointing to the need for research on the social impacts of these events.…”
Section: Resultsmentioning
confidence: 99%
“…Studies performed by Romero-Rodríguez et al [28] demonstrated that arbuscular mycorrhiza inoculation exerts a positive effect on tomato fruit size and caliber by leading to a significant increase of 30% in the axial and equatorial diameters of the fruit. This result is attributed to the combined effect of Gf + Azot + VL, which activates the phytohormones (cytokinins) involved in the cellular division of fruit [29].…”
Section: Discussionmentioning
confidence: 99%